Embracing the Muddle: Learning From the Experiences From Interdisciplinary Teaching and Learning Collaboration - Neill, C; Corder, D; Wikitera, K-A; Cox, S (School of Education, Auckland University of Technology, 2017)
Interdisciplinary, collaborative teaching and learning is recognised as important for twenty-first century tertiary education that seeks to build students’ critical thinking, cultural competence and global understanding. The core elements needed for truly successful collaboration are, however, little understood. This article presents a critical case study of a teaching team’s reflections on experiences in collaborating over two years to deliver a new interdisciplinary undergraduate course focused on culture and society. The findings highlight the importance of building a robust team culture built upon shared leadership, mutual trust and commitment, grounded by strong institutional support, to give any collaboration integrity and sustainability.
Keywords: Tertiary teaching and learning; Collaboration; Interdisciplinary; Intercultural understanding